Camiguin [videorecording] lanzones, bulkan atbp - Medina, Susan Calo.; Philippines. Department of Tourism ([Manila] Travel Time, 1995)
Features Camiguin Island's lanzones festival and its famous landmarks like the seven volcanoes, hot springs resorts, water falls, etc.
VHS.
Keywords: Camiguin Island (Philippines) -- Description and travel